Effect of Vitamin D Supplementation on Clinical Course and T Helper 17/ T-Regulatory Balance in Peripheral Blood of Patients with Crohn’s Disease - Lin, Xiaodong; Wu, Xiaoli; Zhang, Yini; Shao, Xinyi; Wu, Hao; Zhou, Lingli (Turkish Journal of Gastroenterology, 2023)
Background: Vitamin D has anti-inflammatory properties and is involved in immune function, making it a potential therapy for Crohn’s disease. This study aimed to investigate the effects of vitamin D supplementation on immune function and the clinical efficacy of patients with Crohn’s disease. Methods: From September 2017 to September 2021, patients with Crohn’s disease were recruited and randomly divided into 2 groups: the routine treatment group (n = 52) and the vitamin D supplement group (n = 50). In addition to routine treatment, the vitamin D group received oral calcitriol capsule supplementation, while the routine treatment group did not receive any additional intervention. T helper 17/T-regulatory cell level, inflammatory indicators, and nutritional status were compared between the 2 groups, as well as mucosal healing under endoscopy and the life quality of patients. Results: C-reactive protein was significantly lower in the vitamin D treatment group compared to the routine treatment group (6.08 ± 2.72 vs. 18.91 ± 2.66, P < .05). Compared to the routine treatment group, the ratio of T helper 17/T-regulatory cells was significantly lower in the vitamin D group (0.26 ± 0.12 vs. 0.55 ± 0.11, P < .05). After vitamin D treatment, both of the average Crohn’s disease activity index score (from 319.7 ± 72.7 to 179.6 ± 48.5, P < .05) and simple endoscopic score for Crohn’s disease score (from 7.9 ± 2.3 to 3.9 ± 0.6, P < .05) were significantly decreased, while the Inflammatory Bowel Disease Questionnaire score was significantly increased (from 137.8 ± 21.2 to 158.1 ± 25.1, P < .05). Conclusions: Vitamin D has the potential to improve the inflammatory status and immune environment of patients with Crohn’s disease, which can reduce the level of inflammatory factors and help the recovery of symptoms, thus improving the clinical course and quality of life in Crohn’s disease patients. Cite this article as: Lin X, Wu X, Zhang Y, Shao X, Wu H, Zhou L. Effect of vitamin D supplementation on clinical course and T helper 17/ T-regulatory balance in peripheral blood of patients with crohn’s disease. Turk J Gastroenterol. 2023;34(5):463-471.